THE GENETIC HYPOTHESIS OF THE URANIFERUS MINERALIZATION, EASTERN CHALKIDIKI (NORTHERN GREECE) - Persianis, D.; Katsikis, J.; Karageorgiou, D.E. (Bulletin of the Geological Society of Greece, 2010)
This paper presents the genetic hypothesis of αn uranium mineralization observed in Eastern Chalkidiki-Greece. In the area of Stratoni (location Asprochomata) a uranium mineralization is expressing by disseminated primary (orthobrannerite) and secondary (torbernite) U minerals, in the granodioritic body of this area. Genetically it may be the result of uranium redistribution, which occurs in the resisting accecory minerals (e.g monazite) of the granodiorite, by magmatic or meteoric hydrothermal fluids of low temperature. The mineralized granodiorite of Stratoni gives no evidence of a metalliferous pluton, based on the study of hydrothermally altered samples and this ascertainment is a fact that should be confronted with a lot of carefull thought. In the granite of Arnea area, uranium mineralization is in generally absent, excluding some poor one’s, located along the contacts of the granite with small remnants of the hosting rock, expressed in the form of impregnations or veinlets. The possible cause for its formation being the interaction of a secondary low temperature hydrothermal system mainly of meteoric water participation (convective hydrothermal system) with the granite and the hosting wall-rock minerals. The granite of Arnea indicates all the characteristics of a metalliferous granitoid.